A simplified approach for computation of nonlinear ship loads and motions using a 3D time-domain panel method. (1st May 2016) - Sengupta, D.; Datta, R.; Sen, D.
Abstract: Forces and motions on an advancing ship are studied using an approximate nonlinear 3D panel method, formulated based on transient free surface Green's function. Nonlinearities arising from the large-amplitude incident waves are considered in the computations of Froude–Krylov and hydrostatic restoring forces for which a suitable algorithm is developed that can find the exact wetted surface under the incident wave profile. As regards the perturbation potential consisting of the diffraction and radiation effects, although the numerical solution is based on linearized free-surface constraints and discretization of the mean wetted hull under the mean free-surface, a modified form of the body-kinematic condition is applied. Noting that the incident wave-kinematics are largest at the exact free-surface, the adopted procedure is expected to incorporate some of the nonlinearities in the diffraction part of the perturbation potential, albeit partially. Influence of nonlinearities on motions and loads are presented for a Wigley hull and S175 hull in head waves. For the S175 hull, bending moment results are also included. These latter results are particularly important for Class Societies interested in structural loads, and it is found that incorporation of the nonlinearities even within the adopted approximations can result in significantly different pressures and structural loads. Highlights: Simplified 3D method to account nonlinearities in ship motion calculation. Nonlinearities are included without compromising on computation time. Body boundary condition is modified to include nonlinear diffraction forces. A suitable algorithm is developed in order to capture exact free surface. Results are in good agreement with published experimental results.